Do Trainings in the Pre-Employment Card Program Influence the Income of Female Informal-Sector Workers in East Java? - Nabilah, Naurah; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research analyzes the effect of pre-employment training and general training on the income of female informal sector workers in East Java. This research uses a multiple linear regression analysis method with data obtained from the results of the 2023 National Labor Force Survey (SAKERNAS). The research results show that pre-employment training has a positive but not significant effect on income, while general training has a positive and significant effect on income. The conclusion of this research shows that these findings are in line with human capital theory which states that investment in training can increase skills and income. Based on the findings of this research, the government is advised to improve the quality and sustainability of existing training programs and provide post-training assistance to ensure optimal application of skills. For further research, it is recommended to explore other factors that can influence workers' income and analyze the effect of training on opportunities to get a job.